DESIGN AND CONSTRUCTION OF CRAB APARTMENT: MATERIAL AND STRUCTURE ANALYSIS IN ULEE LHEUE, BANDA ACEH CITY - Gunawan, S.Pi., M.M; Fazriansyah Putra, Dedi; Dikta Azmy Anjani (Jurnal Penelitian Progresif, 2023)
Mangrove crab (Syclla sp.) cultivation has problems such as large capital and operational costs for ponds, limited land for cultivation and weather changes that disrupt water quality. This study aims to develop mangrove crab cultivation using an apartment system on land that is not too large as a new innovation for the community. The research method used is a descriptive method. The results of this study explain the construction of crab apartments from the construction of foundations, installation of construction in the form of crab boxes, installation of recirculation media pipes, installation of filter media to full implementation. Crab cultivation with an apartment system can improve water quality to be better with the use of the Recirculating Aquaculture System (RAS) system, namely the repeated use of water with several stages of filtration to reduce ammonia, making crab cultivation with this apartment system one of the solutions to develop and increase production and progress in mangrove crab cultivation.